Developing a Supplemental Archaeological Methodology: A Photogrammetric Study of Shipwrecks Using a Low-Cost ROV - Clevenger, Katherine Lovejoy (East Carolina University, 2017)
In recent years, photogrammetry has been increasingly used as a supplement to traditional archaeological mapping methods. This study aims to show that photogrammetry can be a viable supplement, and in some cases a replacement, for traditional mapping methods when water conditions do not allow for the utilization of standard mapping methods, such as extreme depths and high surge. Additionally, this thesis presents a methodology for using low-cost equipment, in this case an Open-source Remotely Operated Vehicle (OpenROV) 2.8 equipped with GoPro Hero 4 Black cameras to capture high quality video footage of shipwrecks. The best possible resolution and frame rate speed of video footage for photogrammetric purposes is examined. This thesis utilizes numerous computer software, including Agisoft PhotoScan Professional Edition and Adobe Illustrator CC 2017, to create highly detailed 3D models and 2D site plans, respectively. The information provided in this thesis can be used as a guideline for recording submerged cultural heritage with this method. Finally, this thesis explores the use of this methodology to improve management of shipwrecks and addresses the use of 3D models and video footage of shipwrecks for public outreach purposes.
Keywords: Great Lakes; Lake Michigan; Lake Huron; Thunder Bay National Marine Sanctuary; ROV; GoPro action camera; Photogrammetry--Instruments; Shipwrecks; Archaeological expeditions